The Influence Of Advertising And Brand Image On Gen Z's Impulsive Buying Behavior - Asmai Ishak; Sri Rejeki Ekasasi; Anas Hidayat; Lalu Supardin (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of advertising and brand image on impulsive buying behavior of Gen Z. The object of this study is Gen Z consumers who have engaged in impulsive buying behavior, while the subjects are e-commerce consumers in Indonesia. The number of samples in this study was 100 respondents. Sampling was carried out using purposive sampling technique . Data analysis was carried out using multiple linear regression analysis. The measurement scale used a Likert scale of 1-5 and data analysis used SPSS. Based on the results of the analysis carried out, it shows that: first, advertising has a significant effect on impulsive buying behavior of Gen Z. Second, brand image has a significant effect on impulsive buying behavior of Gen Z. Future research needs to include other variables that have not been tested in this study in order to explain more comprehensively the impulsive buying behavior of Gen Z.